Angiotensin II up-regulates monocarboxylate transporters expression in the rat adrenal gland - Kirat, D; Shousha, S (Cellular and Molecular Biology, 2016)
Angiotensin II (Ang II) is a major regulator of aldosterone secretion in the adrenal zona glomerulosa because it up-regulates the expression of a large number of genes involved in aldosterone biosynthesis. The transport of acetate across adrenocortical cells is a crucial step in the de novo synthesis of cholesterol, the steroid precursor of aldosterone. However, whether Ang II can affect this transport remains unknown. The current study aims to investigate the effect of in vivo infusion of Ang II on monocarboxylate transporters (MCT1, MCT2, and MCT4) gene expression in the rat adrenal gland. Immunohistochemical analysis and real-time PCR were used to examine the expression of MCTs at the protein and mRNA levels, respectively. The immunohistochemical analysis showed that higher numbers of cells expressed MCT1, MCT2, and MCT4 proteins in the zona glomerulosa and zona fasiculata of the adrenal cortex of Ang II-infused rats. Furthermore, real-time PCR indicated that in vivo infusion of Ang II increased the mRNA levels of MCT1, MCT2, and MCT4 in the rat adrenal gland. MCT up-regulation might maximize the intracellular transport of acetate in response to the stimulatory effect of Ang II on aldosterone secretion by the adrenal zona glomerulosa..